2015
DOI: 10.1369/0022155415573323
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Angiogenesis and Lymphangiogenesis in Human Minor Salivary Glands with Sjögren’s Syndrome

Abstract: Angiogenesis has been proposed to play a role in the inflammation observed in Sjögren’s Syndrome (SS). However, no studies have validated the degree of angiogenesis in salivary glands with SS. Therefore, the goal of this study was to determine the presence and localization of angiogenesis and lymphangiogenesis in salivary glands with SS. We used frozen tissue sections from human minor salivary glands (hMSG) with and without SS in our analyses. To investigate signs of angiogenesis, hMSG tissue lysates were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…As displayed in Figure 4M-O, MSG lymphatic vessels were consistently and strongly immunostained by D2-40, while CD31 + blood vessels were consistently negative for D2-40. In line with previous observations in human parotid gland and MSGs [7], lymphatic vessels were absent from acinar regions in control MSGs (Fig. 4D, E, G and H).…”
Section: Lymphatic Vascularization and Expression Of Lymphangiogenic supporting
confidence: 93%
See 3 more Smart Citations
“…As displayed in Figure 4M-O, MSG lymphatic vessels were consistently and strongly immunostained by D2-40, while CD31 + blood vessels were consistently negative for D2-40. In line with previous observations in human parotid gland and MSGs [7], lymphatic vessels were absent from acinar regions in control MSGs (Fig. 4D, E, G and H).…”
Section: Lymphatic Vascularization and Expression Of Lymphangiogenic supporting
confidence: 93%
“…In normal conditions, salivary gland lymphatic vessels are selectively localized within the interlobular connective tissue, being absent in lobules and acinar regions 7, 24. Our study revealed that pSS salivary gland tissues display a consistent increase of interlobular lymphatic vessels.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Lymphatic endothelial cells (LECs) of capillaries present loose overlapping intercellular junctions and anchoring filaments that support fluid drainage. LECs specifically express proteins such as lymphatic endothelial hyaluronan receptor 1 (LYVE-1) (1316) and podoplanin, (1719) which have been used as markers for identifying lymphatic vessels in tissue sections. The LEC junctions and permits interstitial fluid uptake when interstitial fluid accumulates within tissues, the extracellular matrix swells and pulls the anchoring filaments.…”
Section: Lymphatic Vasculature and The Peri-articular Lymphatic Systemmentioning
confidence: 99%